Arquitetura residencial em João Pessoa-PB a experiência moderna nos anos 1970 - Araújo, Ricardo Ferreira de (2010)
In the mid-1980s, the magazine Projeto published the Actual Brazilian Architecture catalogue presenting texts by Hugo Segawa and Ruth Verde Zein with a corpus of works and engaged architects of the 1960s and 1970s. To comprehend the Brazilian architectural production post-1964, in those years of the 1980s, became a significant mission to reactivate the Brazilian architectural debate weakened by the military dictatorship. In his doctoral thesis Spadoni (2003) deals with the different ways which characterizes the Brazilian architectural production of the 1970s. Marked by inventiveness, this production was in tune with the modern thinking and in the transition period between the 1970s and the 1980s it synchronized with the international debate about post-modern architecture. Considering Spadoni s doctoral thesis, this work deals with the modern experience observed in the one-family-houses built in the seventies in João Pessoa. Some modern experiences were not clear outside, to observe it, it was necessary to search for the type of experience into the spatial disposition and of the know-how constructive, because into the appearance some houses not make explicit the use of the modern language. Other observed experiences allude to the repertoire of the Brazilian period in the years 1940s-1960s, to the experience of the modern architecture in São Paulo of the 1960s, to the experiences in which the climate of the Northeastern region strongly influenced the architectural conception. We can also find in a reduced number of houses a particular experience: it refers to experiences that expose the constructive doing, which leave the material apparent and apply to the residential type the experience of the industrial pre-fabricated buildings